Factors Affecting Literacy Ability of Elementary School Students in Indonesia - Abidin, Yunus; Rakhmayanti, Fully; Undayasari, Dwi (Mimbar Sekolah Dasar, 2025)
Literacy is a critical competency for success in the 21st century, yet it remains a significant challenge for elementary school students in Indonesia, as their literacy skills are generally low. This research aims to identify the factors influencing the literacy skills of elementary school students. The study adopts a correlational survey method, involving a sample of 293 students. Data was collected through a questionnaire and analyzed using the SEMPLS technique. The results reveal that reading motivation and interest significantly influence students’ reading literacy skills. However, the support from teachers and schools was found to have a limited impact on enhancing students’ reading motivation. These findings suggest that while teacher and school support are important, fostering students’ reading motivation and interest is a key to improving literacy. The study highlights the need for a more tailored approach in nurturing literacy skills, considering the diverse characteristics of students. This research contributes to understanding the underlaying factors affecting literacy and provides insights into educational strategies to enhance reading skills in elementary schools.